2011
DOI: 10.1175/jtech-d-11-00020.1
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Backscatter Measurements from the Advanced Scatterometer on MetOp-A

Abstract: The Advanced Scatterometer (ASCAT) on the Meteorological Operational (MetOp) series of satellites is designed to provide data for the retrieval of ocean wind fields. Three transponders were used to give an absolute calibration and the worst-case calibration error is estimated to be 0.15-0.25 dB.In this paper the calibrated data are validated by comparing the backscatter from a range of naturally distributed targets against models developed from European Remote Sensing Satellite (ERS) scatterometer data.For the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 10 publications
1
14
0
Order By: Relevance
“…d ASCAT backscatter measurements are well calibrated and very stable over time (WILSON et al, 2010). According to ANDERSON et al (2012) the worst-case calibration error is 0.15-0.25 dB and annual changes are in the order of 0.02 dB. This means that ASCAT is very well suited for tracking changes in soil moisture.…”
Section: Instrumentmentioning
confidence: 95%
“…d ASCAT backscatter measurements are well calibrated and very stable over time (WILSON et al, 2010). According to ANDERSON et al (2012) the worst-case calibration error is 0.15-0.25 dB and annual changes are in the order of 0.02 dB. This means that ASCAT is very well suited for tracking changes in soil moisture.…”
Section: Instrumentmentioning
confidence: 95%
“…The ASCAT, flying on the board of the polar-orbiting Meteorological Operational (MetOp) satellite series and using active microwave at a frequency of 5.255 GHz (C-band), was initially designed for monitoring winds over the oceans and was thought to be sub-optimal for soil moisture detection [39], but recent studies have shown that ASCAT soil measurements can be well suited for tracking changes on soil moisture [40] and have a positive impact in practical applications [41]. There are two available ASCAT products currently: the ASCAT-A was launched on the MetOp-A satellite in October 2006, which then became fully operational in May 2007 and continues to operate today, while the ASCAT-B instrument on the MetOp-B satellite became operational in September 2012.…”
Section: Remotely Sensed Soil Moisture Productsmentioning
confidence: 99%
“…There are two available ASCAT products currently: the ASCAT-A was launched on the MetOp-A satellite in October 2006, which then became fully operational in May 2007 and continues to operate today, while the ASCAT-B instrument on the MetOp-B satellite became operational in September 2012. In the study, the raw ASCAT Surface Soil Moisture Level-2 (L2) products (ASCAT-A and ACAT-B) given in swath geometry are available from European Organization for the Exploitation of Meteorological Satellites (EUMETSAT) with a spatial sampling resolution of 12.5 km [41]. Retrievals are available at least once a day (in descending orbit and/or in ascending orbit), and a time-series based change-detection method to remove the adverse influence of surface roughness and eliminate the contribution of vegetation is used.…”
Section: Remotely Sensed Soil Moisture Productsmentioning
confidence: 99%
“…Hence, a method was recently developed to monitor the long-term radiometric stability of ESCAT and ASCAT (Reimer, 2014). The developed method closely follows the principle of relative calibration of scatterometers by making use of natural calibration targets on the Earth's surface (Anderson et al, 2012;Crapolicchio et al, 2012;Lecomte and Wagner, 1998). Natural calibration targets are featured by a temporal stable and homogeneous backscatter response over an extensive area like the Amazon and Congo Rainforest.…”
Section: Instrument Stability Of Escat and Ascatmentioning
confidence: 99%